Bank survey evidence on 'bank lending to SMEs in the European Union' - Rien Wagenvoort (European Investment Bank (EIB), 2003)
This paper presents and analyses the results of a survey of some 400 credit institutions in the European Union carried out by the European Investment Bank in the summer of 2003. An indepth analysis of the survey responses of 74 participating banks leads to the following conclusions: (1) despite the downturn of the European economy, growth of EU bank lending continued at a high pace in 2000-2002; Small and medium-sized enterprises (SMEs) were contributing to credit growth at least as much as large firms; the expansion of firm credit portfolios is expected to slow down in the year 2003 across all size classes, but most strongly for large firms; banks expect unused credit lines to increase in 2003 irrespective of firm size, weakening the argument that credit rationing is hampering economic growth; (2) in contrast to conventional wisdom, survey outcomes suggest that bank consolidation is not necessarily harmful for SME lending; large banks in the EU devote almost 70% of their firm credit portfolio to SMEs (this is comparable to the involvement of small and medium-sized banks), and they do not foresee a reduction in their SME lending; it is likely that the European banking market will be increasingly dominated by commercial banks, but this change should neither be seen as a blow to SME bank finance; on the contrary, survey results indicate that commercial banks assign a higher share of their credit portfolio to small firms than savings banks and co-operative banks; (3) while bankers, on average, expect that a new Basel capital accord will make large firm lending more attractive than SME lending, they are not planning to reduce the share of SME loans in their loan portfolios; (4) although a portfolio of SME loans is hardly more risky than a portfolio of large company loans, the effective interest rate on credits to small (mediumsized) firms is on average 160 (90) basis points higher than on large company credits; neither credit risk nor loan generation costs seem sufficient to explain this mark-up, leading to the conclusion that SME lending is more profitable than large company lending; (5) a substantial number of credit institutions consider to securitize part of the SME loan portfolio in the future, but only on a limited scale.
Keywords: 330